Artificial Intelligence for Postgraduate Literature Review: Unraveling the Path to Automation (Praxis Educativa, 2025)
Exploring previous research is a fundamental step in any research project. Accessing the body of existing knowledge on certain topics helps to define the originality and relevance of one's own research by establishing relationships with what has already been done. The search for bibliographic material, commonly referred to as “conducting a literature review”, can be a complex task, especially for novice researchers. There are tools that can help in this task and, among them, those mediated by artificial intelligence (AI) have been gaining prominence, mainly because they promise to perform the review of previous work more easily and quickly, sometimes even promising that the tool will perform the task autonomously. This paper analyzes three AI-mediated tools that can facilitate the literature review process and discusses the possible pros and cons associated with their use. On the one hand, we hope to highlight the relationship between certain uses of AI-mediated tools and academic literacy practices. On the other hand, we want to encourage critical views on the inclusion or omission of these tools in research and teaching related practices.